Copy raising reconsidered - Nurit Melnik (Journal of Language Modelling, 2023)
There is no consensus in the literature regarding the defining characteristics of copy raising (CR), or in other words what determines whether a CR-like expression is CR or not. As a result, existing analyses target different data sets. In this paper, I propose a different approach to these constructions, which takes a functional perspective. I propose to abandon the term copy raising, which is misleading in a number of ways. Instead, I distinguish between perceptual depiction reports and perceptual inference reports and show that the functions which they fulfill are not particular to CR-like constructions, but are in fact more general. Such an approach, I claim, resolves existing conundrums surrounding CR.